正交面齿轮齿面温升的研究 - 靳广虎; 朱如鹏; 陆俊华 (Jixie chuandong)
This paper presents the theoretical model of calculating the TST（the tooth surface temperature） of face-gear drives based on the theory of heat exchange, and the maximum TST is formulated. The relative speeds on tooth surface and the contact ellipse, which are two important parameters, are calculated too. What’s more, the effects of other main parameters on TST are studied by the analysis of cases.